Effectiveness of line games to improve motor skills of elementary school students - M. Haris Satria; Reza Resah Pratama; Arizky Ramadhan; Defliyanto Defliyanto; Arif Hidayat; M. Haris Satria; Reza Resah Pratama; Arizky Ramadhan; Defliyanto Defliyanto; Arif Hidayat (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2026)
Basic motor skills are an important aspect in the physical development of children and are one of the main goals of learning physical education in elementary school. However, the development of motor skills is often not optimal so that effective and interesting learning models are needed. This study aims to analyze the effectiveness of line game learning to improve basic motor skills of elementary school students. The study used a quantitative approach with a one-group pretest-posttest pre-experimental design. Subjects were 25 elementary school students selected through total sampling technique, consisting of 14 male students and 11 female students aged 10-12 years. Motor skills were measured using observation instruments that included five dimensions, namely strength and flexibility, coordination, balance, movement skills, and courage and readiness to move. The Data were analyzed using descriptive statistics, Shapiro-Wilk normality test,and paired sample t-test. The results showed that motor skills scores improved significantly. The average increase reached 49.53%, and all motor dimensions increased significantly. Conclusion the line game is effective for improving the basic motor skills of elementary school students and deserves to be recommended as a practical and easy-to-apply physical education learning strategy.